Analysis of Land Potential Index on Agricultural Land In Magetan Regency - Muhammad Fahlikal Fiqhan; Agus Anggoro Sigit (Amcolabora, 2022)
Magetan Regency is an area with dominant agricultural land use, but over time, changes in the primary sector economy to an industrial and service sector economy have made conversion of agricultural land to non-agriculture unavoidable. To support sustainable development without disturbing the role of the agricultural sector and so that the role of the agricultural sector does not always depend on the availability of land, it is necessary to evaluate the land so that the available land is designated according to its potential. The aims of this study were (1) to analyze the Land Potential Index in Magetan Regency (2) to analyze the potential of agricultural land in Magetan Regency, and (3) to analyze suitability of agricultural land potential with the spatial plan in Magetan Regency. The method used in this study is a tiered quantitative method, the overlay method, and the cross table method. The land potential index in Magetan Regency consists of 4 potential classes, very low area of 2,494 ha, low area of 22,197 ha, medium area of 24,730 ha, high area of 21,517 ha. The potential of agricultural land in Magetan Regency consists of 4 classes, namely very low potential of 152.6 Ha, low potential of 9,946.1 Ha, medium potential of 14,120.9 Ha, and High potential of 14,129.7 Ha. Agricultural land in Magetan Regency has 36.16% conformity with the regional spatial plans area designation plan and 63.8% discrepancy.